PENGARUH SOLVABILITAS (DER) DAN PROFITABILITAS (ROE) TERHADAP NILAI PERUSAHAAN (PBV) PADA SEKTOR RITEL YANG TERDAFTAR DI BEI THE EFFECT OF SOLVENCY (DER) AND PROFITABILITY (ROE) ON FIRM VALUE (PBV) IN THE RETAIL SECTOR LISTED ON THE IDX - Jauja, Salma; Devi, Rizca Puspita (Journal of Information System, Applied, Management, Accounting and Research; Vol 9 No 3 (2025): JISAMAR (Journal of Information System, Applied, Management, Accounting and Research)DO - 10.52362/jisamar.v9i3.1971, 2025)
This study aims to analyze the effect of solvency, measured by the Debt to Equity Ratio (DER), and profitability, measured by the Return on Equity (ROE), on firm value, measured by the Price to Book Value (PBV), in retail companies under the supermarket and convenience store sub-sector listed on the Indonesia Stock Exchange (IDX) during 2019–2023. This research uses a quantitative approach with multiple linear regression analysis. The data are secondary, obtained from the companies' annual financial reports and processed using SPSS software. The results show that DER has a positive and significant effect on PBV, while ROE does not have a significant effect. Simultaneously, DER and ROE significantly influence PBV. These findings indicate that capital structure, especially debt level, plays a vital role in shaping market perception of company value in this sub-sector. Although profitability remains relevant, it is not the dominant factor in investors’ valuation. This research contributes to understanding the financial structure of the retail sector and provides input for managers and investors in decision-making processes.